Ambivalensi Naratif Novel “Sekali Peristiwa di Banten Selatan” Karya Pramoedya Ananta Toer: Prespektif Dialogisme Bakhtin - Esty Pratiwi Lubarman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine narrative ambivalence in Pramoedya Ananta Toer's novel Sekali Peristiwa di Banten Selatan through the perspective of Mikhail Bakhtin's dialogism, especially the concept of polyphony which includes three main aspects: unfinalizability, the self and other, and carnivalization. This study uses a qualitative descriptive approach with literary text analysis. The third concept used, this study found a relationship between characters in building dialogue and also awareness that is built by considering the position of the narrator designed in building the story. This reflects the importance of Pram's interests who are also narrators in describing the dynamics of post-independence Indonesian society and describing the people's struggle through monologic narratives to show Pram's position during that period. On the other hand, dialogism is reflected in the relationship between people with the same social class as the hero Ranta, but this plurality of positions does not occur in conflicting characters and characters who have higher authority.